A video system for investigating breathing disorders during sleep. - Griffiths, C J (1991)
A system has been developed for investigating breathing during sleep that superimposes physiological signals on a video image of the patient, with the combined image plus sound recorded on video tape for later analysis. Signals normally displayed include oxygen saturation, airflow, chest wall motion, electroencephalogram, and electrooculogram; but others can be recorded if desired. The information is displayed on a timebase appropriate for the recognition and analysis of respiratory events during sleep. In addition, use is made of normally invisible video lines to record the analogue voltage waveforms so that on replay this information can be displayed on a fast timebase for analysing the more rapidly changing waveforms of electrophysiological signals. The system allows detailed polysomnography to be performed in the normal ward setting with the subject monitored overnight by the nursing staff. Subsequent analysis of the synchronised video, audio, and analogue signals allows measurement of the conventional indices obtained by polysomnography and aids their interpretation.